Estrategias de internacionalización de empresas chinas: casos de la industria automotriz en el mercado sudamericano - Regalado Pezúa, Otto (2020)
This study objective is to analyze the internationalization strategies of Chinese automotive companies in the South American market. The transformation and evolution of the industry worldwide as well as the strategies and entry modes to foreign markets are also analyzed. The gathering of information was mainly carried out from secondary sources. The analysis of the Chinese brands: Changan, JAC, Great Wall, Foton and BYD shows that these carmakers have prioritized inorganic growth strategies, specifically the Joint Ventures as well as strategic alliances with concessionaires and the granting of licenses. Chinese automotive industry growth and potential lay the groundwork for further investigation.